Which image? Of which country? Under which spotlight?: Power, visibility and the image of Brazil - Martinez, César Jimenez (Revista Trama Interdisciplinar, 2018)
Since the beginning of this century, and up to the protests that preceded the 2014 World Cup, a common point made by academics, journalists and commentators interested in Brazil was the alleged ‘rise’ or ‘emergence’ of this country as a global power in the international arena. A significant feature in these discussions has been how positive, or not, is the image that Brazil manages to project to the world. In most of these cases, the construction and projection of such images is seen as a necessity for the country in order to successfully entice tourists, attract investment and increase exports, as well as consolidate Brazil’s global political aspirations. In this article, I will sketch out some ideas that can be useful in starting a debate about Brazil´s supposed need to craft and manage a particular image. Most specifically, I would like to examine some of the assumptions underpinning the alleged need to craft national images; the type of nation constructed and projected; as well as the supposed ‘others’ who presumably look at Brazil. The examination of these issues is relevant in highlighting some overlooked structural inequalities and asymmetric power relations involved in the construction and projection of images of the nation. Keywords: Brazil, image, nation, visibility, power